The effects of cinnamon on patients with metabolic diseases: an umbrella review of meta-analyses of randomized controlled trials - Gou, Haobo; Zhong, Ling; Wei, Qiuya; Fan, Yong (Frontiers in Nutrition, 2025)
IntroductionAnimal and clinical studies have demonstrated a range of potential health benefits associated with cinnamon. However, its effects on metabolic parameters such as blood glucose, blood pressure, lipid profiles, and body weight in patients with metabolic diseases remain controversial. To systematically assess the current evidence, we conducted an umbrella review of meta-analyses to comprehensively evaluate the impact of cinnamon supplementation on metabolic outcomes in patients with metabolic diseases.MethodsA systematic search was performed in PubMed, Embase, Web of Science, Scopus, and the Cochrane Library to identify relevant systematic reviews and meta-analyses of randomized placebo-controlled trials investigating cinnamon supplementation in individuals with metabolic diseases. The methodological quality and strength of evidence were assessed using AMSTAR 2 tool (A MeaSurement Tool to Assess systematic Reviews, version 2).ResultsA total of 21 meta-analyses comprising 139 comparisons, were included for qualitative synthesis. The findings indicate that cinnamon supplementation is significantly associated with improvements in fasting blood glucose and lipid profiles, with more pronounced effects observed in patients with diabetes and metabolic syndrome. Subgroup analyses suggest that higher doses (>1.5 g/day) and shorter intervention durations (≤2 months) may enhance these benefits. Additionally, cinnamon shows potential in modulating insulin resistance, antioxidant capacity, and blood pressure regulation.ConclusionThese results underscore the promising role of cinnamon as an adjunctive therapy for metabolic diseases. Future research should focus on well-designed randomized controlled trials with extended follow-up periods to further confirm its efficacy and elucidate underlying mechanisms, thereby providing robust evidence for clinical and public health applications.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251010073, identifier: CRD420251010073.